2005
DOI: 10.1080/10382040508668340
|View full text |Cite
|
Sign up to set email alerts
|

School Choice in Colorado Springs: The Relationship Between Parental Decisions, Location and Neighbourhood Characteristics

Abstract: The influence of location as exemplified by neighbourhood factors and school characteristics on primary education is examined in the context of the school choice movement of the last two decades. The analysis incorporates statistical information about schools and population data from Census 2000 describing neighbourhoods and schools in one district in the State of Colorado in order to minimise structural variables affecting parent decisions, such as tax rates and district leadership. Comparisons of statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…Three explanatory variables exhibit statistically significant positive relationships: education attainment of white population (Beta = 0.26), percent of minority population (Beta = 0.45), and urban locale (Beta = 0.15). Previous research has identified a positive relationship between education attainment and private school enrollment rates (Gemello and Osman 1984;Lankford and Wyckoff 1992;Theobald 2005). The significant negative coefficient of the percentage of minority population in neighborhoods (Beta = −0.08) provides some evidence for the preference theory of school choice and is consistent with the research findings of Fairlie and Resch (2002).…”
Section: Private School Choice In the Columbia Metropolitan Areasupporting
confidence: 82%
See 1 more Smart Citation
“…Three explanatory variables exhibit statistically significant positive relationships: education attainment of white population (Beta = 0.26), percent of minority population (Beta = 0.45), and urban locale (Beta = 0.15). Previous research has identified a positive relationship between education attainment and private school enrollment rates (Gemello and Osman 1984;Lankford and Wyckoff 1992;Theobald 2005). The significant negative coefficient of the percentage of minority population in neighborhoods (Beta = −0.08) provides some evidence for the preference theory of school choice and is consistent with the research findings of Fairlie and Resch (2002).…”
Section: Private School Choice In the Columbia Metropolitan Areasupporting
confidence: 82%
“…Following an approach similar to Ledwith and Clark (2007), the analysis included both neighborhood characteristics (e.g., income and education attainment) and public school attributes (e.g., school quality and percent of minority students) as explanatory variables for obtaining the general underlying causes of private school choice (Table 2). Such an approach underscores that socioeconomic status of neighborhoods and the racial compositions and academic quality of neighborhood public schools are influential in white flight to private schools (Theobald 2005). I hypothesized that the larger the percentage of minority population in neighborhoods and minority students in public schools, the larger the private school participation rate of white students, and, conversely, the higher the academic quality of neighborhood schools, the lower the private school enrollment rates of white students.…”
Section: Methodsmentioning
confidence: 99%
“…On the supply side, researchers have looked carefully at where charter schools locate (Glomm, Harris, & Lo, 2005) as well as the relationship between schools and neighborhoods (McCulloch, 1992;Goldring, Cohen-Vogel, Smrekar, & Taylor, 2006). On the demand side, scholarship has focused on contextual issues associated with geography such as how parents perceive and react to issues of race and social class (Reay, 1996;Schneider & Buckley, 2002;Theobald, 2005;Wells, 1996). Additional work has asked parents to rank factors that influenced their decisions to attend non-neighborhood schools including factors that have geographic components such as transportation, distance from home, and convenience (Blank, Levine, & Steel, 1996;David, West, & Ribbens, 1994;Gill, Timpane, Ross, & Brewer, 2001).…”
Section: The Relationship Between Policy and Geographymentioning
confidence: 98%
“…Whereas middle-class families actively seek out and select alternatives to neighborhood schools, working-class families are more likely to select a school mainly on the basis of distance considerations (Reay and Ball 1997;Allen 2007;Butler et al 2007). Third, even if parents who choose a school stress the importance of school quality in influencing their decision, the main factor influencing the decision, consciously or unconsciously, is the composition of the student body (Lankford and Wyckoff 2001;Holme 2002;Theobald 2005;Harris, Johnston, and Burgess 2007). White, middleclass parents, for example, tend to select schools with both low shares of minority students and few students from low-income households (Waslander, Pater, and van der Weide 2010).…”
mentioning
confidence: 98%